Peningkatan Kemampuan Membaca dan Memahami Gurindam Dua Belas Karya Raja Ali Haji - Amanan; Hermansyah; Juswandi (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
Gurindam Dua Belas is a literary work created by Raja Ali Haji, a writer from the Riau archipelago. This literary work is in the ancient Malay language with the characteristic of many Sufism terms, figurative words and metaphors. The contents of Gurindam Dua Belas contain advice and advice on religious life, the obligations of kings, the characteristics of society, as well as the obligations of parents to children and children's obligations to parents. The participants in this service activity were students of Perhentian Raja 1 Public High School. This activity is really needed by the Provincial Government of Riau in this Reform era to foster and develop Malay culture and Malay culture (BMR). The activities held aim to improve the ability to read and understand Gurindam Dua Belas, and are expected to help students at SMA Negeri 1 Perhentian Raja to interpret/understand, train and practice how to read Gurindam Dua Belas properly. The arrival of the service team from the Faculty of Cultural Sciences, Lancang Kuning University is expected to be able to help the school and especially Perhentian Raja 1 Public High School students to get to know Riau Malay Culture, especially to increase the ability to read and understand Gurindam Dua Belas by Raja Ali Haji.